Different sensorimotor mechanism in fast and slow progression amyotrophic lateral sclerosis. Issue 5 (20th December 2021) - Li, Qianwen; Zhu, Wenjia; Wen, Xinmei; Zang, Zhenxiang; Da, Yuwei; Lu, Jie
Abstract: The huge heterogeneity of the disease progression rate may cause inconsistent findings between local activity and functional connectivity of the primary sensorimotor area (PSMA) in amyotrophic lateral sclerosis (ALS). For illustration of this hypothesis, resting‐state fMRI (RS‐fMRI) data were collected and analyzed on 38 "definite" or "probable" ALS patients (19 fast and 19 slow, cut off median = 0.41) and 37 matched healthy controls. Amplitude of low frequency fluctuations (ALFFs) and functional connectivity strength (FCS) were analyzed within the PSMA. There was a decreased ALFF ( p FDR <.05) and FCS ( p  = .022) in all ALS patients. The two metrics shared about 50% of variance ( R  = .7) and both showed significant positive correlation with ALS Functional Rating Scale‐Revised (ALSFRS‐R) in the fast ( p values <.034) but not in the slow progression groups. Interestingly, when regressing out the ALFF, the PSMA network FCS, especially the inter‐hemisphere FCS, showed negative correlation with the ALSFRS‐R score in the slow ( R  = −.54, p  = .026) but not the fast progression group. In summary, the current results suggest that RS‐fMRI local activity and network functional connectivity accounts for the severity differently in the slow and fast progression ALS patients. Abstract : (1) The decreased ALFF could account for the severity (ALSFRS‐R score) in the fast progression group but not for slow progression group; (2) The network FCS, especially the inter‐hemisphere FCS, showed both pathophysiological effect (i.e., decreased FCS) and a compensatory effect (i.e., negative correlation with severity when the covariate ALFF was regressed out) in the slow progression group, but not in the fast group.